2018
DOI: 10.1016/j.oraloncology.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I antigen processing machinery (APM) component expression and PD-1:PD-L1 pathway activation in HIV-infected head and neck cancers

Abstract: Human immunodeficiency virus (HIV)-infected individuals are at increased risk for developing several non-AIDS related malignancies and are often excluded from cancer immunotherapy regimens. To evaluate the immune competence of this cancer patient population, we evaluated HLA class I antigen presenting machinery (APM) component expression and PD-1:PD-L1 pathway upregulation in HIV(+) and HIV(-) head and neck cancers (HNCs). Sixty-two HIV(+) and 44 matched HIV(-) controls diagnosed with HNC between 1991 and 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Growing evidence suggests that cytokine activation [30], increased immune cell infiltration [31], accumulation of Oxidative Medicine and Cellular Longevity regulatory T cells [7], activation of the PD-1/PD-L1 pathway [32], and upregulation of inhibitory molecules [33] can lead to an immune dysfunction of the TME and produce an inflammatory TME [34]. Based on the above studies, it was confirmed that GNAI2 promotes the interaction between many inflammatory factors to influence the TME in GC.…”
Section: ⁎⁎⁎⁎mentioning
confidence: 99%
“…Growing evidence suggests that cytokine activation [30], increased immune cell infiltration [31], accumulation of Oxidative Medicine and Cellular Longevity regulatory T cells [7], activation of the PD-1/PD-L1 pathway [32], and upregulation of inhibitory molecules [33] can lead to an immune dysfunction of the TME and produce an inflammatory TME [34]. Based on the above studies, it was confirmed that GNAI2 promotes the interaction between many inflammatory factors to influence the TME in GC.…”
Section: ⁎⁎⁎⁎mentioning
confidence: 99%
“…5,13 There is conflicting evidence regarding whether HIV+ HNSCC represents an etiologically distinct disease process from HNSCC in the general population. 3,15 In favor of such a distinction, HIV+ HNSCC has been found to have a unique mutation pattern in the TP53 tumor suppressor gene. 16 This specific mutation in HIV+ HNSCC suggests that HIV infection may play a direct role in pathogenesis of the cancer.…”
Section: Discussionmentioning
confidence: 99%
“…8 There is also evidence to suggest that chronic exposure to HIV viral antigens results in PD1-regulated T-cell exhaustion, contributing to disease progression. 2,3,15,17 However, there is also some evidence against a causal role of HIV in the development of HNSCC. There has been a progressive increase in the incidence of non-HIV related cancers among PLWH despite cART, and compared to PLWH on cART, untreated individuals have not been found to have an increased risk of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind this exclusion is that the extent and type of response mounted by the immune system to lung cancer in these patients is mostly unknown and, therefore, there is a concern that response to immunotherapy may be suboptimal compared to HIV non-infected pa-tients. Yet, pre-clinical studies in PLWH patients with NSCLC [54], anal cancer [55] and head&neck cancer [56] revealed no dramatic differ-ences in tumors' immune infiltrate between HIV-infected vs HIV-uninfected patients. Curiously, in the case-control study with NSCLC patients [54], immune-cell infiltration was more pronounced in tumors from PLWH: there was a higher amount of CD8 + T cells, B cells (CD20 + ) and macrophages (CD163 + ).…”
Section: Implications For Research and Practicementioning
confidence: 99%